Valoración de pasivos ambientales en minas abandonadas ubicadas en áreas circundantes al río Yacuambi, cantón Yacuambi, provincia Zamora Chinchipe. - Torres Cañar, Sandra Cecibel (2014)
The Yacuambi district and its main tributary river, the Yacuambi, is located in the southern east part of Ecuador and it belongs to the gold mining district of Zamora-Chinchipe-Upano. This area is known to have primary deposits (stockworks) that explain their content in alluvial gold, which has been exploited for decades by artisanal miners. The main aim of this study is to assess the environmental mining liabilities in abandoned mines and in the surrounding areas of the Yacuambi River in order to determine both their current status and their priority for environmental recuperation. Abandoned mines were located and characterized by using the methods proposed by Adasme et al. (2010). A probabilistic sampling of them was performed on plants, soil, water and sediment and an environmental impact and risk assessment was performed. Additionally, water samples were also recovered from a pristine site and from an active mine. Moreover, an entire process of alluvial mining was characterized. The alluvial gold mining process in this sector is characterized by the removal and washing of large volumes of gravel and by the use of Hg within a gravimetric process with Zeta processors. Consequences of this process are the presence of 39 abandoned mines in the Yacuambi shores, where thousands of cubic meters of gravel and sand have been stirred and stored. These mines have not been properly closed causing environmental impacts and risks for safety and human health. Our results show high densities of invasive herbaceous species in these impacted ecosystems. Water samples show high concentrations of fats and oils while higher levels of Hg, Cd, Cr, Cu, Pb and Zn were detected in soil and sediment samples. The content of fats and oils may be associated to the use of machinery and equipment during operations while the high trace element concentrations may be due to the exposition of bedrock to erosion, weathering and mining removal, and the high content of Hg is directly related to the use during the process of amalgamation.